Revalidating Blanchard’s Situational Leadership Model: Induction of the Unproductive Follower - Mirčetić, Vuk; Čudanov, Mladen (International Scientific Conference Strategic Management and Decision Support Systems in Strategic Management, 2021)
The globalisation, economic crisis, recession, and the global pandemic had created a new, uncertain environment producing significant disruption in business plans and operations for organisations. The level of uncertainty caused by the pandemic is unprecedented, and it affected organisations to explore diverse approaches to overcome the challenges and discover new opportunities for development in the new normal. Leading effectively in this new and increasingly virtual environment while managing a challenging present requires a particular combination of leadership approaches and skills for adequately identifying situational context because it is a paradoxical setting in which a leader has to provide direction and guidance while acknowledging the unpredictability and ambiguity of the business environment. Organisations have to reexamine their leadership strategy and focus on how to optimise their processes to develop followers and deal with unproductive followers. This paper explores Blanchard’s situational leadership model, which proposes four development level of followers and four accompanying leadership styles. The paper’s core idea is to review the mentioned leadership model and investigate if a fifth follower exists in the model, representing an unproductive follower who is unmotivated and incompetent. Data were collected from questionnaires provided to the new employees in different organisations. The results of the research proved that unproductive followers exist. This paper contributes to the leadership theory by expanding exiting situational leadership theory. Practical implications represent guidelines on how to identify unmotivated and incompetent followers.